HERMAPHRODITISM IN THE THREADFIN FISH, POLYNEMUS MICROSTOMA BLEEKER - Dorairaj, K (Indian Journal of Fisheries, 2011)
The occurrence of hermaphroditism in the small-mouthed thrcadfin fish,Polynemus microstoma Bleeker, collected from the Palk Bay and the Gulf ofMannar is reported for the first time. Hermaphroditism is found in both thelobes of the gonad. The two sex portions in the ovotestis, which are easily distinguishableby their colpur, adhere along the entire length of the gonad inantero-posterior direction. The testicular portion is on the inner lateral side ofthe gonad. The relative size of the male and female portions of the ovotestisvaries in different specimens. It is seen from the microsections that the two sexportions are separated by a thin connective tissue.